Oral Eupolyphaga sinensis extract promotes lumbar interbody fusion by enhancing vascularization of cartilage endplate - Zhen, Ruixin; Li, Jiaqi; Li, Shaorong; Wu, Han; Zhang, Wei (Frontiers in Surgery, 2025)
ObjectiveThis study aims to investigate the effect of oral Eupolyphaga sinensis (ES) extract on intervertebral fusion in a rabbit model.MethodsA rabbit lumbar lateral interbody fusion model was established. Different treatments were administered to each group, including the control group (CON), oral ES extract group (ES), interbody fusion group (IBF) and interbody fusion combined with oral ES group (IBF/ES). Ten weeks after surgery, micro-CT was used to assess intervertebral bone fusion. Bone trabecula parameters, including bone volume fraction (BV/TV), trabecular number (Tb.N) and trabecular thickness (Tb.Th), were measured. Histological analyses, including Masson and HE staining, were used to evaluate angiogenesis and bone growth in the endplate.ResultsThe micro-CT at the 10th postoperative week showed significant bone tissue regeneration and stable fusion in the IBF/ES groups. Fusion scores, BV/TV, Tb.N and Tb.Th were significantly higher in the IBF/ES groups compared to the other groups. In addition, Masson and HE staining indicated evident vascular ingrowth and new bone formation after oral ES extract treatment. Among the four groups, the IBF/ES groups showed the most significant bone formation and the best fusion effect.ConclusionThis study suggested that oral ES extract after spine surgery can significantly enhance the effectiveness and success rate of lumbar lateral fusion surgery by promoting endplate vascularization and bone formation.